The Effectiveness of Model Learning Preser-X Assisted LKS Against Science Process Skills and Understanding Students Concept - Abdillah, Candra; Linuwih, Suharto; Isnaeni, Wiwi (Journal of Primary Education, 2017)
This study aims to know the effectiveness of worksheet-assisted Preser-X model to science process skillss and concept understanding in third grade of primary student on energy material. The research was conducted in Elementary School of Bategede 01 Nalumsari Jepara academic year 2016/2017. The method was Quasi Eksperimental Design. The sample was taken by using saturated sampling. The data were collected such as science process skills with observation and worksheet instrument, and concept understanding with test instrument. The data were analyzed by using one sample t-test for achievement tested for science process skills, proportion test for achievement of classical mastery, independent t test for difference test, simple linear regression for influence test, and N-gain for improvement test. The result showed average score of science process skills was 77% categorized skilled. Classical mastery of concept understanding was obtained 93,10%. There was difference between concept understanding between experimental class and control class and there was influence of science process skills and concept understanding. The improvement in concept understanding in medium category with the percentage 58,62% . The study concluded that the application of worksheet-assisted preser-X models more effective against science process skills and concept understanding of primary students.